Rac1/p21-activated kinase pathway controls retinoblastoma protein phosphorylation and E2F transcription factor activation in B lymphocytes - Zaldua, Natalia (2016)
Small GTPases of the Ras superfamily are capable of activating E2F-dependent transcription leading to cell proliferation, but the molecular mechanisms are poorly understood. In this study, using immortalized chicken DT40 B cell lines to investigate the role of the Vav/Rac signalling cascade on B cell proliferation, it is shown that the proliferative response triggered by B cell receptor activation is dramatically reduced in the absence of Vav3 expression. Analysis of this proliferative defect shows that in the absence of Vav3 expression, retinoblastoma protein (RB) phosphorylation and the subsequent E2F activation do not take place. By combining pharmacological and genetic approaches, phosphatidylinositol-3-kinase and phospholipase Cγ2 (PLCγ2) were identified as the key regulatory signalling molecules upstream of the Vav3/Rac pathway leading to RB phosphorylation and E2F transcription factor activation. Additionally, vav3(-/-) and plcγ2(-/-) DT40 B cells were not able to activate the RB-E2F complex wild-type phenotype when these genetically modified cells were transfected with constitutively active forms of RhoA or Cdc42. However, when these knockout cells were transfected with different constitutively active versions of PLCγ, Vav or Rac1, not only activation of the RB-E2F complex wild-type phenotype was recovered but also the cellular proliferation. Furthermore, by evaluating the effect of two known effector mutants of Rac1 (Rac1(Q61L/F37A) and Rac1(Q61L/Y40C)), the RB-E2F complex activation dependency on p21-activated kinase (PAK) and protein kinase Cε (PKCε) activities was established, being independent of both actin cytoskeleton reorganization and Ras activity. These results suggest that PAK1 and PKCε may be potential therapeutic targets to stop uncontrolled B cell proliferation mediated by the Vav/Rac pathway.